Tea Consumption and Risk of Type 2 Diabetes: A Meta-Analysis of Cohort Studies - Jing, Yali (Springer-Verlag, 2009)
BACKGROUND: Tea consumption has been extensively studied in relation to various diseases, several epidemiologic studies have been performed to investigate the association of tea consumption with type 2 diabetes; however, the results of these studies were not entirely consistent. OBJECTIVE: To conduct a meta-analysis of studies that assessed the association of tea consumption and the risk of type 2 diabetes. RESEARCH DESIGN AND METHODS: We performed a systematic literature search through November 2008 in PUBMED, MEDLINE, EMBASE, and Cochrane Database of Systematic Reviews. The search was limited to English-language studies. Studies were excluded if they were type 1 diabetes, animal studies. Nine cohort studies were identified by two authors, and summary relative risks (RRs) were calculated using a random-effects model. RESULTS: We identified nine cohort studies, including 324,141 participants and 11,400 incident cases of type 2 diabetes with follow-up ranging from 5 to 18 years. The summary adjusted RR did not show that tea consumption was associated with a reduced type 2 diabetes risk (RR, 0.96; 95% confidence interval (CI), 0.92–1.01). Evidence from the results of our stratified analyses revealed that tea consumption ≥4 cups per day (RR, 0.8; 95% CI, 0.7–0.93) might play a role in the prevention of type 2 diabetes. However, no statistically significant association was observed for sex and the follow-up durations stratified between tea consumption and type 2 diabetes. CONCLUSIONS: This meta-analysis indicates that tea consumption ≥4 cups per day may lower the risk of type 2 diabetes.